DAMPAK KEBERADAAN CV. RIAU PLASTIK TERHADAP SOSIAL EKONOMI MASYARAKAT DI SEKITAR KELURAHAN HARJOSARI KECAMATAN SUKAJADI KOTA PEKANBARU - Yelfi Permata Sari; Lapeti Sari; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine how the impact of the plastics factory on the socio-economic communities around the Village Harjosari District of Sukajadi. The data used in this study are primary data and secondary data. Primary data is data obtained from the field of direct data collection obtained by interviews, observations and questionnaires directly spaciousness, while secondary data is data obtained from various agencies or institutions associated with the problems examined include the Central Statistics Agency (BPS) of Riau Province, Department of Industry and Trade of the City of Pekanbaru, and the Village Office Harjosari. Based on the research results can be concluded that the positive and negative impacts on the socio-economic communities around the Village Harjosari District of Sukajadi. There is a positive impact on the socio-economic variables (1) employment, which the company is able to create opportunities for people (2) income, as seen from the increase in people's income from a second job as a result of the establishment of the factory. Moreover, the existence and development of this plastic factory, has indirectly fueled the growth of other businesses that support the community's economy. Meanwhile, in the aspect of health, environment and comfort are not so a negative effect / adverse effects for the surrounding communities, as only a few houses are affected because it is very close to the location of the plastic factory.Keywords : Ekternality, Social and Economic.